ANALISIS PERBANDINGAN NILAI DERAJAT KEJENUHAN MENGGUNAKAN MODEL GREENSHIELDS TERHADAP PEDOMAN KAPASITAS JALAN INDONESIA 2023 - SYAIMA RADESTYA; KRISNA WARIANTI; NURMA YUNITA; AULIA CHOIRI WINDARI; RIBUT NAWANG SARI (Universitas Mahasaraswati K. Mataram, 2024)
Traffic problems in urban areas such as congestion often arise due to the high rate of growth in the population that is not accompanied by the availability of transportation infrastructure. If handling is not done immediately, it will affect the degree of saturation which is one of the criteria for determining the road service index. One of the road segments that are facing traffic congestion problems is Jalan Raya Condet, which is a 2/2 undivided urban road. This study aims to determine the comparison of the degree of saturation of the volume per capacity value between the two methods used. The calculation in this study uses the Greenshields linear model and the rules of the Indonesian Road Capacity Guidelines (PKJI) 2023. From the research results, the value of saturation on the Condet Highway section has exceeded the limit set by the Directorate General of Highways in PKJI 2023. Based on the Regulation of the Minister of PUPR Number 5 of 2023, the number used for road performance limits is the degree of saturation (DJ) ≤ 0.85. However, based on the research results, the Greenshields model and the PKJI 2023 method both provide a degree of saturation value > 0.85 with a road class category of “E”, which means that the vehicle flow on Jalan Raya Condet is not constant and needs to consider increasing road capacity